The Effect Of Utilization Of Productive Zakat Funds On Mustahik Empowerment at BAZNAS Gorontalo Regency - Perdana, Dian Adi; Apriani, Ibnu; Macpal, Sunandar (Department of Islamic Financial Management, Faculty of Economics and Islamic Business, Sunan Kalijaga State Islamic University, Yogyakarta, Indonesia., 2023)
Background: Productive zakat is distributed to mustahiq to support economic development and the benefits can be felt. The aim of productive zakat is to provide a sustainable impact in alleviating poverty and improving the welfare of the people through a consistently productive economy. The phenomenon at BAZNAS Gorontalo Regency is that there needs to be socialization of productive zakat for the development of human resources and a comprehensive productive zakat movement program. Objectives: The aim of the research is to analyze the effect of utilizing productive zakat funds on the empowerment of mustahiq and to analyze the differences in the influence of utilizing productive zakat funds on empowering mustahiq. Novelty: The novelty of the research is to provide zakat analysis on the productive zakat aspect in small areas which has great potential for community economic empowerment and improving the quality of life of the community. Research Methodology / Design: This research approach uses quantitative methods, sampling methods using questionnaires, interviews and observations with quantitative descriptive analysis methods. The population in this study was 15% of the total mustahiq population. Findings: Even though productive zakat has an influence on the empowerment of mustahiq, there are some who fail to maintain, use and allocate productive zakat funds to their businesses so that they do not develop, and there are even minimal changes to the mustahiq. Implication: The impact of the research is the need to continue to increase the allocation of zakat funds for productive activities in order to build economic independence and welfare of mustahiq, maximize the use of zakat funds with regular training for mustahiq, and monitoring in the form of capital coverage reports provided in the form of financial reports to be more professional in managing zakat funds and the use of productive zakat funds is businesslike and serious in carrying out its business to empower mustahik.